Investigation of the protein expression level in lesions of patients with psoriasis vulgaris by proteomics technology - Junbo DU; Dalei ZHANG; Hengpo ZHANG; Jing LI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To investigate the differentially expressed proteins in lesions of patients with psoriasis vulgaris (PV) by proteomics technology. Methods: A total of six patients with PV and six patients with pigmented nevus presented to our hospital between June 2020 and September 2020 were enrolled. The lesions of PV and pigmented nevus-adjacent normal skin tissues were obtained by surgical removation. These differentially expressed proteins between the lesions of patients with PV (n=4) and normal skin tissues (n=4) was explored by proteomics technique. These differentially expressed proteins were further analyzed by GO and KEGG enrichment analysis. The protein protein interaction (PPI) analysis was used to screen out key proteins in the lesions of PV. Key proteins were independently verified in the lesions with PV (n=2) and normal skin tissues (n=2). Results: When compared with normal skin tissues, 291 proteins were significantly up-regulated and 163 proteins were significantly down-regulated in lesions of PV. These involved biological processes were mainly associated with neutrophil activation, neutrophil-mediated immunity, TNF-α-mediated signaling pathway, B cell-mediated immunity, epithelial cell differentiation and keratinization. The involved pathogenesis was mainly associated with IL-17 signaling pathway, oxidative phosphorylation, PPAR signal pathways and others. The PPI results showed that S100A7, S100A9, neutrophil gelatinase-associated lipocalin, cytochrome c oxidase subunit NDUFA4, fatty acid-binding protein 5, peroxisomal acyl-coenzyme A oxidase 1, platelet glycoprotein 4, cathepsin B, eosinophil cationic protein, haptoglobin, haptog-1lobin, apoptosis-associated speck-like protein containing a CARD may paly the key role in the pathogenesis of PV. When compared with normal skin tissues, these expression levels of S100A7 (t=5.54, P<0.05), S100A9 (t=45.23, P<0.05), cathepsin B (t=4.23, P<0.05), haptoglobin (t=4.12, P<0.05) and arginase-1 (t=6.65, P<0.05) proteins in the lesions of PV were significantly increased, and the differences were statistically significant. Conclusions: The mutiple immune-related pathways and differentially expressed proteins may paly an important role in the pathogenesis of PV, which could provide new therapeutic targets for PV.